Paciente femenino de seis años de edad diagnosticado con estrabismo congénito. - Saquinaula Torres, Germania Mercedes (2020)
The present clinical case is about a six-year-old female patient diagnosed with congenital strabismus, which is extremely important because the strabismus must be corrected at an early age either by visual therapy or by surgical means, since if prevention measures are not taken in the early stage, these can lead to more serious problems such as loss of parallelism, loss of binocular vision, loss of depth vision or, what is worse, functional problems such as amblyopia due to lack of level stimulation. of fovea given that the eye when being in another gaze position does not receive the corresponding stimulus but rather that stimulus is paracentral, consequently the eye does not learn to see correctly, in addition to avoiding a series of signs such as turning or tilting the head, torticolis, to see better in a certain gaze position causing symptoms such as headache and dizziness, the objective of this clinical case is to ide To identify the type of strabismus, and the visual alteration suffered by the patient, objective and subjective examinations were carried out to assess her visual range, in addition to complementary tests such as biomicroscopy, ophthalmoscopy, Bruckner's reflex, Worth's light test, Hirschberg's test. For this, the inductive deductive methods and retrospective data of the patient were used for analysis, finding as a result that he suffered from headache, burning and redness of the eyes, after a meticulous study of the examinations and diagnosis, it is concluded that the defect The girl's visual is a tropia accompanied by mixed astigmatism.